Analysis of Deixis in Joker's Main Character 2019 - Wijayanto, Robertus Vito (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research examines five forms of deixis in the Joker movie data from Joker (2019) movie conversations or scripts is used in this qualitative research. It aims to find out deixis words within the deixis journal in other movies, the conversation in the movie directly between main character and the interlocutor. Data source from conversation could be in the movies or scripts. The data collection is done by entering the data in the Joker film, then looking for suitable methods to analyze the film, and looking for results or findings in the conversations of both the main character and his interlocutors. These five types of deixis are often used to analyze the linguistics of movies, for examples are: person deixis, spatial or place deixis, temporal deixis, social deixis, and discourse deixis. The results are to find five types deixis part in conversation with pictures and their explanation, such as; person deixis, spatial or place deixis, temporal or time deixis, social deixis, and discourse deixis. The method uses content analysis; one example of the use content analysis that can be used to analyze research is exploring deixis in dialogue or conversation in script. What deixis do prominent characters in "Joker" movies utilize and what are the most common. Arthur uses personal deixis to express his loneliness and perplexity, saying, “The worst part of having a mental illness is people expect you to behave as if you don't”. Temporal deixis appears when Arthur refers to traumatic past moments, suggesting temporal disorientation as part of the symptoms of pseudobulbar affect and childhood trauma. Meanwhile, spatial deixis further emphasizes alienation: for example, when performing in front of Murray Franklin, “here” transforms the stage of the confessional universe into an arena of humiliation.